KUALITAS SUSTAINABILITY REPORTING DALAM RISET PELAPORAN KORPORAT - Nina Febriana Dosinta; Nur Fitriana Hamsyi; Juanda Astarani (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2022)
The Sustainability Reporting (SR) quality had questioned because there is no standard in preparing SR enforced by standard setters in Indonesia. The SR quality had anticipated by reviewing corporate reporting research. Therefore, this study investigates the quality of SR in corporate reporting research. This study uses a systematic literature review from 2007-2020 through articles based on selected databases. The results showed that the measurement of the SR quality had dominated by the use of codification from the Global Reporting Initiatives (GRI). The accountability of corporate reporting, especially SR, cannot only be reviewed through GRI. The quality of SR in corporate reporting research shows that the codification proposed by other researchers besides GRI can be an alternative as a form of corporate reporting accountability. SR quality as an indicator of accountability for the implementation of the company's sustainability activities. The sustainability reporting quality is not a goal, only a tool to assess the sustainability of activities that an entity has carried out.